2014
DOI: 10.1177/1073191114552472
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of the Patient Version of the Working Alliance Inventory–Short Form Revised

Abstract: The working alliance concerns the quality of collaboration between patient and therapist in psychotherapy. One of the most widely used scales for measuring the working alliance is the Working Alliance Inventory (WAI). For the patient-rated version, the short form developed by Hatcher and Gillaspy (WAI-SR) has shown the best psychometric properties. In two confirmatory factor analyses of the WAI-SR, approximate fit indices were within commonly accepted norms, but the likelihood ratio chi-square test showed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 44 publications
3
74
1
5
Order By: Relevance
“…The instrument captures Bordin's () concept of the therapeutic alliance with the three dimensions Bond , Task, and Goal . In several studies, a two factor model with a Bond factor and a Goal & Task factor showed the best psychometric fit (e.g., Falkenström, Hatcher, & Holmqvist, ; Mander et al ., ; Webb et al ., ). The items of the WAI‐SR were rated on a five‐step scale ranging from 1 (does not apply) to 5 (applies fully).…”
Section: Methodsmentioning
confidence: 99%
“…The instrument captures Bordin's () concept of the therapeutic alliance with the three dimensions Bond , Task, and Goal . In several studies, a two factor model with a Bond factor and a Goal & Task factor showed the best psychometric fit (e.g., Falkenström, Hatcher, & Holmqvist, ; Mander et al ., ; Webb et al ., ). The items of the WAI‐SR were rated on a five‐step scale ranging from 1 (does not apply) to 5 (applies fully).…”
Section: Methodsmentioning
confidence: 99%
“… * Includes aspects of both body and mind ** May be present and experienced on the self-engagement level, but need to be consciously expressed for it to be measured. 1 (Bradley & Lang, 1994) 2 (Allen, Chambers, & Towers, 2007) 3 (Miller, Maletic, & Raison, 2009) 4 (Lane, Quinlan, Schwartz, Walker, & Zeitlin, 1990) 5 (Benjamin, 1995) 6 ( Politi, Enright, & Weihs, 2007) 7 (Carlson & Brown, 2005) 8 (Bond et al, 2011) 9 (Fonagy et al, 2016) 10 (Jackson & Marsh, 1996) 11 (Falkenström, Hatcher, & Holmqvist, 2015) 12 (Hatcher & Gillaspy, 2006) 13 (Klein, Mathieu-Coughlan, & Kiesler, 1986) 14 (Babyak, Snyder, & Yoshinobu, 1993) 15 (Snyder, 1995) 16 (Tsai, Knutson, & Fung, 2006) 17 (Fegg, Kramer, Bausewein, & Borasio, 2007) 18 (Eriksson & Lindström, 2006) …”
Section: Tablementioning
confidence: 99%
“…Furthermore, we believe that negative emotions can be channeled to the art materials, art making process and product leaving more “room” for positive emotional regard between client and therapist (Schaverien, 1987). The working alliance can be measured with the Working Alliance Inventory, short form revised (WAI-SR) (Falkenström, Hatcher, & Holmqvist, 2015; Hatcher & Gillaspy, 2006). …”
Section: Tactile Engagementmentioning
confidence: 99%
“…When evaluating the facets of the alliance, we found that early empathy experiences were significantly associated with goals and tasks (but not bond ). Large correlations have been reported between goals and tasks (e.g., Patterson, Uhlin, & Anderson, ), and some factor analyses have shown that goals and tasks items load on the same factor (e.g., Andrusyna, Tang, DeRubeis, & Luborsky, ; Falkenström, Hatcher, & Holmqvist, ), which has been labeled agreement (Webb et al., ). This potential link between empathy and agreement lends credence to the idea that empathy has pacing‐like effects (see Wong, ).…”
Section: Discussionmentioning
confidence: 99%